2020
DOI: 10.1155/2020/2172156
|View full text |Cite
|
Sign up to set email alerts
|

A New Continuum Model considering Driving Behaviors and Electronic Throttle Effect on a Gradient Highway

Abstract: In order to explore the potential impact of sloping road on traffic flow, an improved car-following model considering electronic throttle (ET) dynamics and driver’s driving characteristics on slope is proposed. Based on the improved car-following model, a new continuum model is established through the conversion relationship between microscopic variables and macroscopic variables. Firstly, the stability condition of the model is obtained by using the linear stability theory, after that the evolution process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In [118], the traffic flow characteristics in the non-lane-discipline-environment with a slope were analyzed. Based on the extended FVD model and considering the driver's offensive characteristics [119], the slope FVD model [116], and the equation of vehicle movement and ETOA information [86], Jiao et al [120] proposed a new extended slope FVD model considering a driver's offensive characteristics and ETOA information and derived the corresponding macro flow model.…”
Section: Slopementioning
confidence: 99%
“…In [118], the traffic flow characteristics in the non-lane-discipline-environment with a slope were analyzed. Based on the extended FVD model and considering the driver's offensive characteristics [119], the slope FVD model [116], and the equation of vehicle movement and ETOA information [86], Jiao et al [120] proposed a new extended slope FVD model considering a driver's offensive characteristics and ETOA information and derived the corresponding macro flow model.…”
Section: Slopementioning
confidence: 99%
“…Kang et al derived a macro model utilizing the micro-macro relation based on Sun's model [137] to explore the traffic flow characteristic affected by information about the average velocity of multiple preceding vehicles in the current lane [70]. Jiao et al derived a macro model for describing characteristics of traffic flow with slope based on the extended car-following model with consideration of the ETOA information [138]. Sun et al derived a macro model to analyze how the traffic flow affected the information of two preceding vehicles based on the extended model incorporating the same information [139].…”
Section: Analyzing the Characteristics Of Traffic Flowmentioning
confidence: 99%
“…Meanwhile, it is also very important to analyze the overall evolution of traffic flow from a macro perspective. [13][14][15][16][17][18][19] Qin et al [13] discussed the effect of electronic throttle on the stability of mixed traffic flow. Jiao et al [14] proposed a new macro model, which contains electronic throttle (ET) and ramp factors.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Qin et al [13] discussed the effect of electronic throttle on the stability of mixed traffic flow. Jiao et al [14] proposed a new macro model, which contains electronic throttle (ET) and ramp factors. The results indicated that the ET effect play an important role in alleviating traffic congestion to a certain extent.…”
Section: Introductionmentioning
confidence: 99%